Emergent Meningoencephalitis Following Spinal Anesthesia: A Case Report - Yara Mouawad; Mahmoud El-Hussein; Joelle Kalaji; Patrick Nasrallah; Cima Hamieh; Eric Revue (Case Reports in Infectious Diseases)
Conclusion: This case highlights the potential for meningoencephalitis following spinal anesthesia, a rare but serious complication. Adhering to stringent aseptic guidelines and protocols is critical to prevent such infections. Prompt diagnosis and treatment are essential to mitigate the risks of severe neurologic damage and improve patient outcomes. Further research is needed to better understand the infection control measures that can prevent iatrogenic meningitis in spinal procedures.